Gender roles in the prehistoric fishing community: A case study from Gilimanuk Site, Bali: Peran gender di komunitas nelayan prasejarah: Studi kasus dari Situs Gilimanuk, Bali - Dicky Caesario Wibowo (BRIN, 2021)
Gender roles are defined as social construction of activities and statuses associated to specific genders in a society. This article aims to investigate gender roles among prehistoric community in Gilimanuk Sites based on the division of labor by sex. This research uses bioarchaeological approach by comparing entheseal changes on 42 male and female individuals. The result shows there is no specific activity associated to certain sex in daily subsistence. This indicates the gender construction in the prehistoric fishing community in Gilimanuk Sites.